Women Participation In Organizational Activities In A Democratic Society As Perceived By Stakeholders’ In North-West Nigeria (International Journal of Scientific Research and Management (IJSRM), 2019)
The study assessed women participation in organizational activities in a democratic society as perceived by stakeholders’ in North-West Nigeria. The research design that was used for this study is the descriptive survey design The design allows for the use of questionnaires, which generated valid data that were analyzed. The population of this study consisted of all the stakeholders in education that comprised the students, graduates, teachers, school administrators, Ministry personnel, Quality Assurances officers in the North-west zone of Nigeria. The target population consisted of all stakeholders in the following states: Sokoto, Zamfara, and Kano in the North-west zone of Nigeria. Multi-stage sampling technique was adopted needed for this study. The total population of stakeholders in North-west Nigeria was 1,970 out of this numbers, 1261 respondents were proportionately selected for the study. Two research questions were raised as follows: (1) What are the stakeholdersperception of the influence of women participation in organizational activities in North-west Nigeria. (2).What are the stakeholdersperception of empowering women to engage in politics an enduring democracy in North-west Nigeria. The findings of this study revealed that more than half of the stakeholders perceived the influence of WCCE graduates on participation in organizational activities in North-west, In addition the result also indicated that more than half of the stakeholders perceived the contributions of graduates of WCCE to graduates empowerment in politics in North-west,The study recommended that Women were adjudged by the respondents as organizers of homes, and families. Therefore women graduates participation in organization activities in their communities should double their effort so as to continue to serve as a role model to other women in the society for socio-economic development.. NGOs and State government should provide additional support for women to have access to loans and market facilities. Providing them with soft loans would be required.